Serum and tissue level of insulin-like growth factor-I (IGF-I) and IGF-I binding proteins as an index of pancreatitis and pancreatic cancer - Karna, Ewa (Blackwell Science Inc, 2002)
Previously we have found deregulation of collagen metabolism in human pancreatitis and pancreatic cancer tissues. Insulin-like growth factor-I (IGF-I) is known to stimulate collagen biosynthesis through interaction with IGF-I receptor. IGF-I binding proteins (BPs) regulate the activity of IGF-I. We investigated whether serum and tissue IGF-I and IGF-BPs as well as tissue IGF-I receptor expression may reflect disturbances of collagen metabolism in patients with pancreatitis and pancreatic cancer. In pancreatitis tissue, a significant increase in IGF-I and IGFBP-3 content was accompanied by a distinct increase in IGF-I receptor expression, compared to control pancreas tissue. In contrast, serum from patients with pancreatitis did not show significant increases in IGF-I and IGFBP-3 levels, however, significant increases in IGFBP-1 level (2.5 fold). Moreover, a distinct decrease in radioactive IGF-binding to the BPs, compared to control serum, was found. Pancreatic cancer tissue and serum of patients with pancreatic cancer showed significant increases in IGF-I, IGFBP-3 and IGFBP-1 content, accompanied by dramatic increases in IGF-I tissue receptor expression, compared to controls. In serum of patients with pancreatic cancer distinct increases in radioactive IGF-binding to 46 kDa BP, compared to control serum, were observed. The data suggest that disturbances in tissue collagen metabolism during pancreatic diseases may result from deregulation of IGF-I homeostasis and that elevated serum levels of IGF-I, IGFBP-3 and IGFBP-1 may serve as markers of pancreatic cancer